Gamification Research in Sustainable Educational Settings: A Thematic Analysis Approach - Karakose, Turgut; Papadakis, Stamatios (International Journal of Interactive Mobile Technologies (iJIM), 2025)
Gamification has gained increasing prominence in educational research as a strategy for enhancing learner engagement, motivation, and performance. Despite a growing body of literature, a comprehensive understanding of how gamification themes have evolved over time remains limited. This study conducts a bibliometric and science mapping analysis using SciMAT to examine the thematic evolution of gamification in education based on 3,414 peer-reviewed journal articles indexed in Scopus. The analysis spans three distinct periods—1962–2009, 2010–2019, and 2020–2025—revealing a progression from peripheral and exploratory themes to more mature, theoretically grounded, and diversified research clusters. Key motor themes such as gamification, motivation, and humans persist throughout all periods, while emerging themes include special education, virtual reality, and autonomous learning. The study underscores the field’s conceptual maturation and diversification in response to technological advances and pedagogical shifts, particularly in the post-pandemic era. Findings offer strategic insights for educators, researchers, and policymakers seeking to design inclusive and sustainable gamified learning environments.